External technology sourcing through alliances and acquisitions: a technology interdependence perspective. (19th September 2018) - Lin, Liang-Hung; Ho, Yu-Ling
Abstract : Alliances and acquisitions are important strategies for firms to obtain external technologies. For better understanding these strategies, this study develops a technology interdependence perspective to explain how managers decide their ally-or-acquire choices and the needed levels of hierarchical control in alliances and acquisitions. By further classifying technology interdependence into dimensions of joint technology dependence and technology dependence asymmetry between exchange partners, this study suggests that the former (later) dimension may drive more (less) hierarchical control in these decisions. This study also provides important insights by suggesting that these decisions are determined by the relative strength of joint technology dependence and technology dependence asymmetry.